2023
DOI: 10.1155/2023/7571696
|View full text |Cite|
|
Sign up to set email alerts
|

Circulating miR-340-5p and miR-506-3p as Two Osteo-miRNAs for Predicting Osteoporosis in a Cohort of Postmenopausal Women

Abstract: Objective. An increasing risk of developing osteoporosis which is characterized by bone production weakness and microarchitectural deterioration is found among postmenopausal women. MicroRNAs (miRNAs) are secreted into the circulation from cells of various tissues in response to local disease severity including bone diseases. Herein, we set out to identify candidate miRNAs predictable for osteoporosis incidence in postmenopausal elderly women. Methods. The circulating miRNA expression profiles deposited in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Early diagnosis and timely intervention are beneficial for preventing the development of osteoporosis (Sakka, 2022). In recent years, numerous studies have demonstrated that CUL1, PTEN, STAT1, MAPKAPK2, RARRES2, FLNA, STXBP2, miR-340-5p, and miR-506-3p could potentially serve as biomarkers for osteoporosis (Wang et al, 2022;Zhao Y. et al, 2022;Lu et al, 2023;Yuxuan et al, 2023). However, the majority of these molecular markers have not yet been validated using clinical samples.…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis and timely intervention are beneficial for preventing the development of osteoporosis (Sakka, 2022). In recent years, numerous studies have demonstrated that CUL1, PTEN, STAT1, MAPKAPK2, RARRES2, FLNA, STXBP2, miR-340-5p, and miR-506-3p could potentially serve as biomarkers for osteoporosis (Wang et al, 2022;Zhao Y. et al, 2022;Lu et al, 2023;Yuxuan et al, 2023). However, the majority of these molecular markers have not yet been validated using clinical samples.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%